Budaya Organisasi dan Manajemen Sumber Daya Manusia Berbasis Humanis sebagai Transformasi Strategis POLRI di Era Society 5.0 - M. Firman Ar Rasyid; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the synthesis of organizational culture and human resource management based on humanism as part of the Indonesian National Police (POLRI) strategic transformation in the Society 5.0 era. The study was conducted using a literature review method with a qualitative descriptive approach through the collection of various relevant literature sources, such as scientific journals, books, and official police documents. The data search process was carried out systematically through Google Scholar, ResearchGate, and various other academic portals with a focus on the themes of organizational culture, human resource development, public communication, and digital transformation within the police institution. The data obtained were analyzed using content analysis and thematic analysis techniques on twelve selected literatures to identify key patterns related to professionalism, discipline, motivation, public service, and technology adaptation within the POLRI. The results of the study indicate that the POLRI transformation strategy requires strengthening an organizational culture that is adaptive, transparent, and oriented towards human values. Human resource development through continuous training, increasing digital competency, open public communication, and training-based discipline enforcement are important factors in building a professional and humanistic image of the police. In addition, the application of public service technology is considered capable of increasing the effectiveness of member performance if supported by work motivation, integrity, and a conducive organizational environment. This research also found that an overly rigid bureaucratic culture remains an obstacle in navigating the dynamics of the digital society. This study emphasizes the importance of reforming organizational culture and human resource management to be more flexible, collaborative, and responsive to societal needs in the era of Society 5.0.